Unpacking Classroom Talk: A Systematic Review of Thematic Discourse Analysis in English Language Teacher-Student Interaction - Dian Ratnawati (Journal of Educational Sciences, 2026)
Teacher–student interaction plays a critical role in shaping learning experiences, influencing students’ cognitive, emotional, and communicative development. This study aims to synthesize findings from recent empirical and conceptual studies through a Systematic Literature Review (SLR) focusing on discourse analysis in English language classrooms. A total of selected articles published between 2020 and 2025 were reviewed to identify patterns, power relations, communicative strategies, and pedagogical implications of classroom discourse. The findings reveal that teacher talk remains dominant in many contexts, characterized by directive speech, display questions, and limited dialogic space. However, several studies highlight the importance of fostering student-centered communication, utilizing technology to enhance interaction, and understanding cultural dynamics in shaping classroom discourse. Power relations, emotional contagion, and deixis were found to significantly influence participation and meaning-making processes. Moreover, discourse-based instructional models and critical discourse analysis approaches demonstrate potential in encouraging reflective pedagogy and communicative competence. Overall, this review underscores the need for teachers to develop awareness of linguistic choices and interactional patterns to build inclusive, dialogic, and empowering learning environments. The synthesized insights offer practical implications for educators, policymakers, and curriculum designers aiming to improve teaching practices and enhance student engagement.